The imperative to prevent diabetes complications: a broadening spectrum and an increasing burden despite improved outcomes. Issue 6 (6th April 2015) - Twigg, Stephen M; Wong, Jencia
Summary: Diabetes mellitus and its complications are common; the complications are, of themselves, a major reason to manage diabetes. Recent data from Australia and similar developed health care systems overseas indicate that morbidity and mortality outcomes relating to diabetes complications are improving. However, these benefits are offset by increasing numbers of people diagnosed with diabetes, resulting in an increased disease burden with significant health care implications. Thus the imperative to prevent diabetes and diabetes complications has never been greater. Furthermore, the recognised spectrum of diabetes complications is broadening, especially complications relating to lipid levels, insulin resistance and the metabolic syndrome. Clinicians now need to be aware of both traditional complications (eg, nephropathy and cardiovascular disease) and non‐traditional complications (eg, polycystic ovary syndrome, non‐alcoholic fatty liver disease, some cancers and eating disorders). Complications outcomes could be further improved by decreasing the evidence–treatment gap — for example, by increasing personalisation of care in managing diabetes complications.